El material didáctico en el aprendizaje de la lecto escritura del quinto grado de la escuela Luis Humberto Benítez Costa, Loja 2022 – 2023 - Infante Jumbo, Juan Pablo (2023)
The use of didactic resources is an innovative method in the Ecuadorian educational system since it allows to the teacher share the teaching and learning process in an understandable way, it allows the student to comprehend all the topics easily, in order to have a meaningful learning. This research work is about: The didactic material in the learning of reading and writing skills with students of fifth grade at Luis Humberto Benitez Costa School, in the city of Loja, during the 2022 – 2023 school year. The objectives were: To determine the incidence of didactic material in the learning of reading and writing skills with students of fifth grade at Luis Humberto Benitez Costa School, in the city of Loja, during the 2022 – 2023 school year. The type of study is descriptive with a non-experimental transactional design, it was worked with the following methods: scientific, inductive, deductive, analytical, synthetic, statistical. With the purpose to elucidate the investigated problem a survey and interview were applied to a population of 25 human beings, 24 students and one teacher, with these techniques it was determined that the use of didactic material is fundamental in order to have creative and innovative ways for teaching and learning process and thus the student can achieve meaningful learning, so the teacher must be in pedagogical update to be able for sharing the knowledge in a correct way. It is concluded that, to solve the problem found in this research work, employing a constant and innovative use of didactic material in the learning of reading and writing skills, all the students would be focused on improving their knowledge. Key words: Innovator, give, assimilate, elucidate.